2007
DOI: 10.1051/0004-6361:20066616
|View full text |Cite
|
Sign up to set email alerts
|

Study of the K-H${_2}$ quasi-molecular line satellite in the potassium resonance line

Abstract: Context. The optical spectra of L and T-type dwarfs exhibit a continuum dominated by the far wings of the absorption profiles of the Na 3s-3p and K 4s-4p doublet perturbed by molecular hydrogen and helium. The presence of a broad absorption feature in the blue wing of the K 4s-4p doublet may be attributed to the K-H 2 quasi-molecular line satellite as we predicted in a previous work. Aims. The position of the predicted line satellite was not in good agreement with the observed feature. This was a motivation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 41 publications
5
31
0
Order By: Relevance
“…1), mainly in the slope of the repulsive walls, leads to this close agreement in the line wings and the prediction of the quasi-molecular line satellite at 0.23 µm. In Allard et al (2007c), we have shown that ab initio K-H 2 potentials systematically less repulsive than the pseudo-potentials of Rossi & Pascale (1985) allowed a K-H 2 quasi-molecular line satellite to be predicted, which closely matches the position and shape of an observed feature in the spectrum of the T1 dwarf ε Indi Ba (Allard et al 2007a). More recently, in Allard et al (2016b), the position of the predicted line satellite was confirmed by a laboratory measurement.…”
Section: Satellite Bands and Density Dependencesupporting
confidence: 62%
“…1), mainly in the slope of the repulsive walls, leads to this close agreement in the line wings and the prediction of the quasi-molecular line satellite at 0.23 µm. In Allard et al (2007c), we have shown that ab initio K-H 2 potentials systematically less repulsive than the pseudo-potentials of Rossi & Pascale (1985) allowed a K-H 2 quasi-molecular line satellite to be predicted, which closely matches the position and shape of an observed feature in the spectrum of the T1 dwarf ε Indi Ba (Allard et al 2007a). More recently, in Allard et al (2016b), the position of the predicted line satellite was confirmed by a laboratory measurement.…”
Section: Satellite Bands and Density Dependencesupporting
confidence: 62%
“…In this continuation of previous work (Allard et al 2003(Allard et al , 2007c, we illustrate the evolution of the absorption spectra of K-H 2 collisional profiles for the densities and temperatures A&A 589, A21 (2016) prevailing in atmosphere of cool brown dwarf stars (Sect. 4).…”
Section: Introductionmentioning
confidence: 82%
“…Alkali-H 2 collisional profiles have been the subject of previous studies by Burrows & Volobuyev (2003) and Allard et al (2003Allard et al ( , 2007c. Absorption profiles of sodium and potassium perturbed by helium and molecular hydrogen were presented in Burrows & Volobuyev (2003) using multiconfiguration selfconsistent field Hartree-Fock potentials in the Szudy theory (Szudy & Baylis 1975.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The line shapes of these alkali metals were calculated at different temperatures and interpolated for intermediate values 21,22 . Their spectral contribution becomes important in the visible wavelength range (Fig.…”
mentioning
confidence: 99%